Renewable Energy Consumption and Its Role in Driving Green Economic Growth in BRICS Nations - Saboor, Abdul; Manzoor, Zainab; Rehman, Abdul (Pakistan Journal of Humanities and Social Sciences, 2025)
In recent years, a significant boost in environmental degradation has been seen globally. This change in the environment not only disturbs the lifestyle of the people but also impacts the economic conditions of the nations. For this aim, green economic growth (GEG) is introduced that balances economic growth and environmental dynamics. GEG not only escalates economic growth but also preserves the usage of natural resources that help to mitigate environmental degradation and provide a better living standard to future generations. For this purpose, this research explored the impact of renewable energy sources (REC), GDP per capita (GDPC) and trade openness (TOS) on the GEG in the BRICS countries by taking the annual data from 1995 to 2021. The outcomes are concluded by using the PMG-ARDL. The PMG-ARDL is appropriate due to its uniqueness by combining the long run-homogeneity and the short-run heterogeneity in the panel data sets and making it ideal to analyze the relationship in the heterogeneous panels. The outcomes from PMG-ARDL stated a positive and significant relationship between REC, GDPC and TOS on GEG in the long run. While seeing the short-run findings, TOS and GDPC have a significant while REC has an insignificant relationship with GEG in BRICS nations. Considering these outcomes, BRICS nations should make strict policies and regulations to enhance sustainable, green and eco-friendly production practices that enhance the usage of RECC, TOS and GDPC; this contributes toward sustainable development i.e. GEG.